Pengaruh Kualitas Produk Dan Pelayanan Terhadap Kepuasan Komsumen Harian Surat Kabar Lahat Pos - Nindyawati (Sekolah Tinggi Ilmu Ekonomi (STIE) Serelo Lahat, 2020)
Newspapers are one source of information for the public that is actual and factual, so that various kinds of information presented in it. Lahat Pos is one of the media companies in the form of community newspapers in Lahat District precisely located in Lahat City which produces the daily newspaper of Lahat Pos circulating every day and distributed throughout the Regency of Lahat, Empat Lawang, and Kota Pagaralam. This study was conducted to determine the Influence of Product Quality and Service to Satisfaction of Daily Consumer of Newspaper Lahat Pos. The sample used is 40 customers. The analysis method is Multiple Linear Regression Analysis, T-Test, and F-Test. The resulting regression equation is Y = 64.319 + -0.488 X.1 + 0.055X.2 + e. The t-test results suggest that product quality has no significant effect on customer satisfaction, while service has positive significant effect on customer satisfaction. F-test results show that both independent variables do not affect simultaneously to customer satisfaction. The result of determination coefficient analysis (R2) can be obtained Adjusted R Square (R2) of 0.013 which means that variable of Product Quality and Service to Consumer Satisfaction equal to 13%. While the rest of 87% explained by other factors outside of research such as place and facilities, already have a loyal customer, and so forth.